How to optimize ecological compensation to alleviate the ecosystem services supply and demand mismatch in the Luo River Basin? - Huimin Zhou; Xuning Qiao; Yongju Yang; Jinyuan Zhang; Qianxi Zheng; Hongfei Gao; Tongqian Zhao (Ecological Indicators)
The ecological compensation (EC) mechanism is crucial for balancing regional development, enhancing ecosystem services (ESs), and achieving sustainable development goals. However, how to optimize ecological compensation to alleviate the ecosystem service supply and demand mismatch remains unsolved. This study examines the Luo River Basin and applies theories of externalities and environmental justice. The InVEST and spatial analysis models are used to evaluate the supply and demand of four ESs—carbon sequestration (CS), food production (FP), soil retention (SR), and water yield (WY)—from 2000 to 2020. The ecological service flow (ESF) path in the Luo River basin is simulated using the breakpoint formula and field strength model, comprehensively considering terrain and land use resistance. Construct an EC model integrating comprehensive natural differentials, economic levels, and social development coefficients, and prioritize compensation. Employ the Gini coefficient to adjust for distributional equity. There is a mismatch between supply and demand for ESs in the Luo River Basin from 2000 to 2020, with supply services CS, SR, and WY trending downward and FP trending upward. Demand service CS is trending up and FP, SR and WY are trending down. ESF flows weakened with distance and flowed primarily from the southwest to the northeast of the Luo River Basin, with the highest number of service flows in WY. The total EC reaches 393.4 million yuan. Song County receives the highest EC (95.8 million yuan), while Luolong District has the highest compensation payment (147.4 million yuan). The study further identified priority areas for compensation. The study is expected to provide theoretical references for ecological management and compensation in watersheds, as well as strategic pathways for realizing environmental justice.